PENGEMBANGAN MODUL AJAR BERBANTUKAN CANVA PADA MATA PELAJARAN IPAS DALAM KURIKULUM MERDEKA KELAS IV SEKOLAH DASAR - Moh Rosyid Mahmudi; Yulia Darniyanti; Anisa Oktaviani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is because they only received teaching modules from the government, but no one has developed teaching modules in schools. Elementary School SDN 10 Sitiung really needs the development of teaching modules with the help of Canva in the subject of natural sciences in the independent curriculum for grade IV elementary schools. Therefore, in an effort to overcome these problems, this study developed a teaching module with the help of Canva for the Science Subject in the Independent Curriculum for Grade IV Elementary Schools with valid and practical criteria. This type of research is development. This type of research is Research and Development (R&D) research using the ADDIE development model which consists of several stages: Analysis, Design, Development, Implementation, Evaluation. The test subjects were class IV educators at SDN 10 Sitiung. The assessment instrument is in the form of validation and practicality sheets. The assessment instrument was validated by three validators, content validator, language validator and graphic validator, then practice sheets were determined by practitioners. The results of the validity of the Teaching Module carried out by three validators obtained an average validity value of 83.1% classified as very valid, the average educator practicality value was 93.7% classified as very practical. It can be concluded that the Canva-assisted teaching module on science subjects in the independent curriculum for grade IV elementary schools can be applied in the learning process.